Analysis-Associated Factors Interfering With Diffusion Tensor Indices of Peripheral Nerves - Luka Pušnik; Lucija Laubry; Igor Serša; Armin Alibegović; Erika Cvetko; Žiga Snoj; Nejc Umek (Image Analysis and Stereology)
Diffusion tensor imaging (DTI) enables a non-invasive assessment of tissue architecture based on water diffusion. High-resolution magnetic resonance imaging (MRI) systems have enhanced the visualization of nerve compartments. This study investigates the influence of region of interest (ROI) selection on DTI indices in ex vivo peripheral nerves. Cadaveric median nerves (n=10) were harvested and immersed in fluorinated-carbon liquid, and 9-mm segments were scanned with a 9.4-T MRI system. Diffusion-weighted signals were summed, and diffusion tensors were calculated for anatomical compartments using different delineation techniques. Following the initial scan, five samples were scanned for a second time using an identical protocol. The analysis showed that the inclusion of an inert background into the ROI significantly reduces fractional anisotropy (FA). Significant differences in diffusion tensors were observed between the initial and intermediate segments, with FA and mean diffusivity (MD) differing by as much as 25.2% and 25.6%, respectively. Tracing the fascicles without the interfascicular epineurium exhibited an 8.8% lower FA compared to the delineations of the epineurium. Second MRI scans showed significant changes in dif-fusion tensors with higher eigenvalues D1-D3 and MD; along with lower FA. In conclusion, the intermediate portions of the nerve demonstrated greater consistency in DTI indices and are recommended for analysis over the initial portions. Using an inert liquid can minimize background effects, but the inherent diffusion properties of the tissue must be carefully considered. Prolonged scanning times can alter diffusion tensors, likely due to autolytic processes, underscoring the importance of consistent pre-scanning conditions and acquisition protocols. Additionally, maintaining consistency in delineations is paramount, regardless of whether the tracing method includes or excludes the interfascicular epineurium.